On solving split equilibrium problems and fixed point problems of nonspreading multi-valued mappings in Hilbert spaces - Suantai S. (2017)
© 2016, Suantai et al. In this paper, we introduce and study iterative schemes for solving split equilibrium problems and fixed point problems of nonspreading multi-valued mappings in Hilbert spaces and prove that the modified Mann iteration converges weakly to a common solution of the considered problems. Moreover, we present some examples and numerical results for the main results.